Some Physical System by Fourier Series in Weight Function for Electric Field and its Application - Edae, Tadesse Lamessa (International Journal For Research In Mathematics And Statistics, 2020)
The Fourier series is a tool for mathematics, electrical and other engineering sciences .And also it’s beneficial in differential equations because it can transform them into equations which are easier to solve. Many of the phenomena studied in engineering and science are periodic in nature the current and voltage in an alternating current circuit. These periodic functions can be analyzed into their constituent components (fundamentals and harmonics) by a process called Fourier analysis. In this work, Fourier-series representation of a weight function is used to highlight and clarify the controversial problem of finding the value of the function at a point of discontinuity. Several physical situations are presented to examine the consequences of this kind of representation and its impact on some widely well-known problems whose results are not clearly understood.